2020
DOI: 10.1088/1742-6596/1618/6/062036
|View full text |Cite
|
Sign up to set email alerts
|

Wind farm blockage effects: comparison of different engineering models

Abstract: The work presents four engineering methods to estimate the induction zone in front of a wind turbine and account for the wind farm blockage effect. The methods comprise the vortex cylinder model, vortex dipole model, self-similar model, and wake projection model. The majority of the models presented account for yaw misalignments and ground effect. Actuator disk simulations are used to verify the individual models. The performance of each model is evaluated both in terms of precision and computational time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 11 publications
4
25
0
Order By: Relevance
“…Traditionally, wind farm models employed in the wind energy industry assumed that the wind speed upstream of an entire wind farm was unaffected by the presence of the wind farm itself. Now this assumption is known to be incorrect, and several correction methods to account for the wind farm blockage have been proposed in the last few years [4,5]. However, none of the existing correction methods are universal or robust enough to predict the wind farm blockage effect accurately under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, wind farm models employed in the wind energy industry assumed that the wind speed upstream of an entire wind farm was unaffected by the presence of the wind farm itself. Now this assumption is known to be incorrect, and several correction methods to account for the wind farm blockage have been proposed in the last few years [4,5]. However, none of the existing correction methods are universal or robust enough to predict the wind farm blockage effect accurately under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of blockage, most often defined as the slowdown of streamwise velocity in the region upstream from a turbine or farm, has received increased attention for reasons ranging from the impact on wildlife (Quon et al, 2021) to the discrepancy between predicted and observed power in newly-constructed plants (Bleeg et al, 2018). Previous work has examined engineering models to capture the effects of blockage (Branlard et al, 2020). Formalizing a method to measure this blockage effect in a manner that facilitates layout optimization enables turbine array designs that balance total power output while also mitigating the impact on upstream conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, there are attempts to incorporate the blockage effect in the engineering models. The four models reviewed by Branlard et al [5] consider the blockage effect through modeling the speed from the induction zone. Segalini [6] creates a new model that includes the blockage effect, which is based on the linearized RANS equation.…”
Section: Introductionmentioning
confidence: 99%